Interpreting in legal and healthcare settings : perspectives on research and training - Ng, Eva N. S.; Crezee, Ineke (Benjamins translation library, 2020)
"The importance of quality interpreting in legal and healthcare settings can never be stressed enough, when any mistake - no matter how small - can compromise the delivery of justice or put someone's health at risk. This book addresses issues arising from interpreting in legal and healthcare settings by presenting cutting-edge research findings in interpreting and interpreter education in a number of countries around the world - including those which are relatively new to the field. It contains selected papers from a conference dedicated to such themes - the First International Conference on Legal and Healthcare Interpreting - as well as other invited papers related to the fields of legal and healthcare interpreting. This book is useful not only to scholars and educators, interpreters and translators working in legal or healthcare settings, but also to legal and healthcare professionals who work with interpreters in their day-to-day work, including judges, lawyers, police officers, doctors, midwives and nurses"--